DIMENSIONAL ANALYSIS TO ESTIMATE THE UNSATURATED HYDRAULIC CONDUCTIVITY OF A SANDY LOAM SOIL IN THE AGRICULTURAL FIELD - Al-Dosary,Naji Mordi Naji (2022)
ABSTRACT Hydraulic conductivity in unsaturated soil controls water movement and measuring it in agricultural fields is a challenging task requiring time-consuming, costly, and skilled experimentation. This study was conducted to reduce the cost of experimentation through the development of an estimation model. The developed model is based on dimensional analysis to determine the value of hydraulic conductivity of unsaturated soil as it relates to soil moisture content, irrigation water electrical conductivity, and suction rate (pressure head). Data points were acquired from measurements of cumulative infiltration in the field, using a mini disc infiltrometer. The developed model gave a mean discrepancy ratio of 1.10 (the acceptable range is 0.5–2.0) and a mean percentage of relative errors of 9.96%. These values indicate that the dimensional analysis model is reliable for the prediction of sandy loam soil’s unsaturated hydraulic conductivity.